Rancang Bangun Sistem Monitoring Arus Dan Tegangan Pada Panel ATS – AMF Hybrid Berbasis Internet Of Things - Arif Hidaya (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In general, to determine current and Voltage conditions, manual checks using a multimeter are typically performed. Therefore, a tool or system is needed to monitor current and Voltage more practically without requiring direct or manual checks. Based on this background, a Design and Development of a Current and Voltage Monitoring System for ATS-AMF Hybrid Panels Based on the Internet Of Things (IoT) was created, utilizing the PZEM-004T sensor as a component for measuring source Voltage. The PZEM-004T sensor is used to measure or read the AC 3-phase current and Voltage in the ATS-AMF panel, with the NodeMCU ESP8266 serving as the microcontroller. This study aims to simplify the measurement of current and Voltage in the ATS-AMF panel. The method used involves data collection through manual testing of current and Voltage using a multi-tester and clamp meter. The tests include no-load testing and testing with an electric motor load. The results of manual measurements using a multimeter and clamp meter showed Voltage readings of R-S (407 V), S-T (411 V), and T-R (409 V), and current readings of R (0.54 A), S (0.51 A), and T (0.53 A). Measurements using the PZEM-004T sensor, as displayed in the Blynk application, indicated Voltage readings of R-S (409 V), S-T (408 V), and T-R (410 V), and current readings of R (0.58 A), S (0.60 A), and T (0.60 A). This IoT-based current and Voltage Monitoring system is highly efficient as it facilitates real-time Monitoring of current and Voltage, making the task significantly easier. The system achieved an average error rate of 0.40% for Voltage measurements and 0.11% for current measurements